Pembaruan Fiqih Indonesia (Telaah Tafsir Al-Bayan Karya T.M Hasbi Ash-Shiddieqy) - Sobari sutarip (JURNAL INDO-ISLAMIKA, 2020)
This paper discusses the methodology of interpreting the Koran by Teungku Muhammad Hasbi Ash Shiddieqy in Tafsir al Bayan. Tafsir Al Bayan is one of the interpretations of the work of the nation's children in the mid-20th century using Indonesian. Tafsir Al Bayan contains a complete interpretation of the Koran and 30 juz translations published in 1966. Tafsir Al Bayan is Hasbi's second work in the field of interpretation after he succeeded in writing his first work, Tafsir An Nur complete 30 Juz in 1956. The purpose of this research is to know the methodology of the exegete in interpreting the Koran. The method used in this research is the method of text analysis of the Al Bayan interpretation in particular, as well as referring to Hasbi's other works and studies on the study of the Al Bayan Tafsir and Hasbi's thoughts in various articles and journals. Research on the interpretation of T.M Hasbi in Tafsir Al Bayan produced several findings, namely: 1) Ittijah or the direction of T.M Hasbi's goals in writing Tafsir Al Bayan are; first, to perfect the translations of the Koran that have developed in Indonesian society. Second, provide concise comments explaining the meaning of the verses which require explanation according to the new style of interpreting the verses of the Quran. 2) The method used by T.M Hasbi in interpreting the Koran is the tahlili method by comparing the opinions of other mufassirs. 3) The approach used by T.M Hasbi in interpreting the Qur'an in general is the bir ro'yi approach, but the elements of bil ma'tsur and linguistic elements also color in Hasbi's interpretation. 4) Interpretation style Ttafsir al Bayan is identical to fiqh style which is full of tajdid and ijtihad nuances. T.M Hasbi's appeal and strong encouragement for Tajdid and ijtihad are an important element in distinguishing Tafsir Al Bayan from others.